Whether hysteroscopy improves fertility outcomes in infertile women: a meta-analysis and systematic review - Wang, Yidi; Tang, Zunhao; Wang, Chanchan; Teng, Xiuxiang; He, Junqin (Frontiers in Endocrinology, 2024)
Purpose Infertility is affecting more and more couples of appropriate age. Hysteroscopy (HSC) has certain effects on the uncompleted pregnancy and live birth caused by uterine microenvironment. Based on the evidence, this paper systematically evaluates the effectiveness and safety of HSC intervention on the fertility outcome of female infertility. Methods Randomized controlled trials (RCTS) of hysteroscopy intervention in female infertility were included in the literature database. The retrieval time was from the establishment of the database to December 10, 2022. RevMan 5.4 software was used for statistical analysis to study the effects of HSC on clinical pregnancy rate, live birth rate and abortion rate. Results A total of 14 RCTS were included. Five studies evaluated the effect of HSC on live birth rate, and HSC had an overall positive effect on live birth rate. Fourteen studies evaluated the effect of HSC on clinical pregnancy rates, and preoperative HSC was associated with significant improvements in pregnancy rates for both first-time IVF/ICSI patients and repeat IVF/ICSI patients. Eight studies showed no significant difference in the effect of HSC on miscarriage rates. Conclusion As a visual examination/treatment technique, HSC can improve the clinical pregnancy rate and live birth rate in most studies, while the risk of abortion is within the acceptable range, and can be used as a recommended examination method for infertile women.